COLONIAL MILITARY INTELLIGENCE IN THE ZULU REBELLION, 1906 - Thompson, P. S. (Scientia Militaria - South African Journal of Military Studies, 2014)
In the Zulu Rebellion of 1906, the Natal Militia defeated the Zulu rebels without British imperial forces having to intervene in the conflict. The colonial forces were well adapted to the local circumstances, but in one important respect they drew heavily on imperial experience, namely military field intelligence. Colonial military intelligence was modelled on imperial military intelligence in the South African War (1899–1902). The Natal Militia, reorganised in 1903, lacked an intelligence department at the outbreak of the rebellion, and had to improvise a system quickly. The improvisation in the field proved very effective, providing valuable information on the enemy’s strength, dispositions and intentions, and so contributed to the timely victory of the colonial forces at the battle of Mome (10 June 1906). This article gives the imperial background and describes the organisation (staff, officers and operatives, scouts and spies) and operations (collection, interpretation and dissemination of information) of colonial military intelligence in the field during the crucial second phase of the rebellion.